(untitled) (LEARNing Landscapes, 2016)
Creative engagement accesses profound knowing and understanding that is not reachable by words alone. Situated in Connelly and Clandinin’s Narrative Inquiry, we use creative self-expression in teaching-learning, research, and practice. We examine artful approaches used in research with students and nurses in mental health, and in our classrooms. Through such artful inquiry we push the boundaries of what it means to co-create knowledge. Our students, future caregivers, learn how knowing has both epistemological and ontological dimensions. In our experience, it is embodied knowing that has the greatest potential for making connections with those in our care.